Egyptian diplomacy towards the Al-Nahda dam and its challenges - Mahmood, pshdar Hussain; Al-Barzanji, prof. Dr. Dana Ali Saleh (The International and Political Journal, 2023)
This research is an attempt to review and study Egyptian diplomacy towards the Al-Nahda Dam crisis after 2011. This crisis has been existing as one of the main issues of Egyptian diplomacy. And because of the importance of this topic, the research arises the following questions: Has Egyptian diplomacy succeeded in employing its tools to solve the Ethiopian Al-Nahda Dam crisis and achieve its interests? What are the challenges facing this diplomacy? In order to obtain convincing answers to these questions, this research attempts to present a basic hypothesis, which states that:“Egyptian diplomacy has used a set of its external tools to address the file of the Ethiopian Al- Nahda Dam and protect the country’s interests, but it failed in achieving its goals in convincing Ethiopia to abide through the principles of international water law. This failure was due to a number of internal and external challenges it faced when it decided to resolve the crisis. To study this issue, the research relies on two approaches, the descriptive method, and the system analysis method to investigate the validity of the main assumption of the research. As a result, the research approved the validity of its hypothesis.